Intensity-based rebating of emissions pricing revenues - Christoph Böhringer; Nic Rivers; Carolyn Fischer (ZBW - Leibniz Information Centre for Economics, 2021)
Carbon pricing policies worldwide are increasingly coupled with direct or indirect subsidies for emission-intensive and trade-exposed firms. We analyze the incentives created by novel forms of emissions intensity-based rebating (IBR) and contrast them with more common approaches like output-based rebating (OBR), abatement-based rebating (ABR), or lump-sum rebating (LSR). We rank the different rebate schemes in terms of output protection, emission intensity reduction, and emissions price pressure. We find that intensity-based rebating schemes typically combine elements of OBR and ABR. Given the same sectoral emissions target, revenue-neutral forms of IBR that are proportional to output or emissions lead to the same outcome as conventional outputbased rebating, but with lower emissions prices. Outcomes with a simpler form of IBR that subsidizes intensity reductions directly can resemble those with OBR when reductions are less ambitious, while with deeper intensity reductions, outcomes approach those of LSR. With ABR, the emissions price fully offsets the abatement rebate and the resulting allocation is identical to LSR. We supplement partial equilibrium theoretical analysis with numerical simulations to assess the performance of different mechanisms in a multi-sector general equilibrium model which accounts for economy-wide market interactions.
Keywords: H23; D21; D58; Q48; 330